Linguistic awareness and English spelling difficulties of Iranian EFL students in Malaysia - Alipour, Maryam; Khazriyati Salehuddin,; Siti Hamin Stapa, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The ability to spell properly is usually regarded as a good indicator of one’s level of education (Fagerberg, 2006). In this study spelling difficulties are classified as phonological, morphological, and orthographical difficulties in order to examine the correlation between spelling difficulties and the linguistic awareness of Iranian EFL students in Malaysia. The participants of the study were 41 Iranian EFL students (20 males and 21 females) who were selected purposefully from an Iranian secondary school in Kuala Lumpur, Malaysia. A pre-test post-test design adapting a set of tests from Tabrizi et al. (2013) was used to examine the correlation between linguistic awareness and spelling difficulties. Forty words were selected from the second-year English textbook of Iranian EFL students in the pre-test and post-test. Based on the results of the pre-test, the most frequent types of errors were identified. They were related to the Visual Memory, Training Error, Listening Accuracy, Visual Accuracy, Dysgraphia and Visual Sequential Memory. Analysis of the data showed a significant correlation between the participants’ linguistic awareness and phonological, morphological and orthographical spelling difficulties. It was concluded that children’s developing awareness of linguistic features can help them become more proficient language learners. Findings from this study can assist EFL teachers in mitigating the spelling difficulties among young learners.